Contexto de trabalho docente e assédio moral: construção e validação de instrumentos - Cunha, Esthela Sá (2023)
Assessing the teachers' work context is a strategic resource for promoting health, quality of life, and people management. Studies have shown that the work context affects job satisfaction, productivity, students' educational outcomes, and teachers' mental health. Bullying at work is another issue that deserves to be highlighted since it is a type of violence still veiled among teachers. In addition, most research and interventions on school violence analyze students as victims of aggression. There is also a need for nationally constructed or validated instruments to measure workplace bullying among teachers. The present investigation is composed of two studies. The sample of both studies consisted of 15,176 primary school teachers from Brazilian public scho ols. Teachers answered a self administered online questionnaire that contained the Teachers' Remote Work Context Assessment Scale (TRWCAS), the Negative Acts Questionnaire Revised (NAQ R), the Self Reporting Questionnaire (SRQ 20), and sociodemographic questions. Study 1 aimed to build and validate the TRWCAS. Study 2 aimed to analyze the psychometric properties of the NAQ R for the sample of teachers. We performed exploratory, confirmatory, and convergent validation factor analyses. Study 1 showed that the TRWCAS presented the factors work organization, working conditions, and socio professional relationships, which explained 55.8% of the total variance. The model in the confirmatory factor analysis showed adequate fit indices (RMSEA = .073 CI 90%: .072 .074; SRMR = .057; CFI = .985; TLI = .984). The measure showed evidence of convergent validity with the SRQ 20, an instrument that measures common mental disorders and satisfactory internal consistency (work organization: α = .92, ω = .94; work conditions: α = .83, ω = .87; socioprofessional relationships: α = .91, ω = .94). The results of study 2 demonstrated that the instrument had a two factor structure: personal bullying and workplace bullying, which explained 69% of the total variance. The NAQ R show ed satisfactory fit indices (RMSEA = .041, 90% CI: .039 .042, SRMR = .043, CFI = .995, TLI = .995) and adequate internal consistency (personal bullying: α = .98, ω = .98; workplace bullying α = .92, ω = .92). The measure also showed evidence of convergent validity with the SRQ 20. The results obtained from the application of the instruments will be able to guide state and municipal education departments in developing interventions that improve the quality of life at work and in the identification and prevention of violence in the work environment.